2021
DOI: 10.15695/jstem/v4i1.05
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of a Peer-Learning Research Community on the Development of Students’ Researcher Identity, Confidence, and STEM Interest and Engagement

Abstract: While the impact of authentic research experiences in STEM on student engagement and interest in science has been documented, less is known about the role of peer communities in fostering this interest and engagement. This research explores the idea that a strong peer community can catalyze deep learning and engagement in scientific research among high school students. The program engaged 20 high school students in a year-long community-based participatory research project in public health each year. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…STEM outreach programs for high school students from underrepresented groups have the potential to positively impact students' researcher identities by providing meaningful, authentic, and positive research experiences and mentorship (Basu and Calabrese Barton, 2006). For example, one such program, San Francisco Health Investigators, demonstrated an increase in researcher identity among high school students through a year-long community-based participatory research project that emphasized belonging in peer relationships and the larger research community (Koo et al, 2021). Their findings also support the importance of building community among students who are marginalized in STEM outreach programming (Koo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM outreach programs for high school students from underrepresented groups have the potential to positively impact students' researcher identities by providing meaningful, authentic, and positive research experiences and mentorship (Basu and Calabrese Barton, 2006). For example, one such program, San Francisco Health Investigators, demonstrated an increase in researcher identity among high school students through a year-long community-based participatory research project that emphasized belonging in peer relationships and the larger research community (Koo et al, 2021). Their findings also support the importance of building community among students who are marginalized in STEM outreach programming (Koo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Researcher Identity. The Researcher Identity Scale measures students' agency, community, interest, aspiration, and self-perceptions as someone who can contribute to investigations about a topic (Koo et al, 2021), and has been validated for use with high school students as a Likert-scale and Guttman scale (Wilson et al, 2022). In this study, researcher identity was derived by averaging the Guttman scale answers to twelve questions (Wilson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The developers considered RIS to be one unified idea made up of four strands: fit & aspiration, community, self, and agency. For more information on the project under which this development work took place and for more information about the RIS latent variable, its components, and its construct map, see Koo et al (2021). The construct map for this construct is shown in Figure 2.…”
Section: An Example Construct Mapmentioning
confidence: 99%
“…First, we give some brief background on this instrument to make the example clearer and more concrete. The instrument was developed to measure researcher identit y by the San Francisco Health Investigators (SFHI) Project (Koo et al, 2021) and is referred to as the Researcher Identity Scale (RIS). The developers considered RIS to be one unified idea made up of four strands: fit & aspiration, community, self, and agency.…”
Section: An Example Construct Mapmentioning
confidence: 99%
“…Building from Lave and Wenger's (1991) and Wenger's (1998) research examining situated learning and communities of practice, recent research has narrowed the focus on the meaning‐making that occurs within communities and the negotiations around who one is (i.e., identity) within them (Koo et al, 2021; Mark, 2018). Bucholtz and Hall (2005) outlined several principles used in scholarship to approach identity work, one of which centers on positionality.…”
Section: Theoretical Groundingmentioning
confidence: 99%